Cost sharing in health insurance: An instrument for risk selection? - Karolin Becker; Peter Zweifel (University of Zurich, Socioeconomic Institute, 2005)
Health insurance is potentially subject to risk selection, i.e. adverse selection on the part of consumers and cream skimming on the part of insurers. Adverse selection models predict that competitive health insurers can eschew high-risk individuals by offering contracts with low deductibles or co-payment rates, while attracting low-risk individuals with higher copayments, resulting in a separating equilibrium. This contribution seeks to determine whether in competitive Swiss social health insurance policies with deductibles in excess of the legal minimum do indeed serve as an instrument of risk selection. In a discrete choice experiment, effected in 2003, some 1,000 individuals were given the hypothetical choice of alternative insurance contracts that differed both in terms of deductibles and copayments and in bene.ts covered. Results suggest that healthy individuals, i.e. those not having consulted medical services during the past six months, were more likely to select a policy with a high deductible. Compensation demanded for voluntarily accepting an increase in the annual deductible also varies with socioeconomic characteristics and increases with the current level of deductible, as predicted by theory and constituting evidence in favor of the risk selection hypothesis. The experiment allows to compute necessary premium reductions and provides guidance for the pricing policy of insurers when offering differentiated products.
Keywords: C35; C93; D61; I11; I18; 330; health insurance; deductible; copayment; willingness-to-pay; adverse selection; Private Krankenversicherung; Adverse Selektion; Willingness to pay; Test; Schweiz